Cattle infestation by Hyalomma ticks and prevalence of Theileria in Hyalomma species in the east of Turkey - Aktas, M; Dumanli, N; Angin, M (Elsevier Science Bv, 2004)
A total of 2388 cattle and 442 shelters, from two provinces (Elazig and Malatya) endemic for tropical theileriosis in the east of Turkey, were studied for Hyalomma tick populations from July 1993 to July 1995 in Elazig and from May 1998 to January 1999 in Malatya. Four thousand five hundred and eighty one of 7455 Hyalomma ticks were collected from cattle, the other ticks (2874) were collected from shelters. All of the ticks collected from shelters were Hyalomma anatolicum anatolicum. Two thousand eight hundred and ninety five (63.1%) of 4581 Hyalomma ticks collected from cattle were H.a. anatolicum. 23.8% (1047/4581), 11.7% (536/4581) and 0.6% (3/4581). of Hyalomma ticks were Hyalomma anatolicum excavatum, Hyalomma detritum and Hyalomma marginatum marginatum, respectively. A total of 5909 Hyalomma adult ticks collected from cattle (3362/5909) and shelters (2447/5909) were dissected and salivary glands were stained with Methyl-green/Pyronin method. Thousand one hundred and fifty (46.9%) of 2447 H.a. anatolicum collected from shelters and 412 (19.1%) of 2147 H.a. anatolicum collected from cattle were positive for Theileria infection. Twenty (2.4%) of 820 H.a. excavatum and 23 (4.6%) of 495. H. detritum collected from cattle were positive. The mean number of infected acini per infected male and female ticks collected from cattle were 11.3 and 22.4 in H.a. anatolicum, 4 and 6.8 in H.a. excavatum, 17.9 and 18.3 in H. detritum, respectively. In H.a. anatolicum collected from shelters, the above rates were 11.8 and 17.6 in male and female ticks, respectively. The prevalence and intensity of Theileria infection was greater in female ticks than in males. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Theileria; vector; Hyalomma; salivary gland; cattle